PENDAMPINGAN MANAJEMEN USAHA KELOMPOK USAHA BERSAMA (KUB) KOPI ARABIKA DI KABUPATEN TEMANGGUNG - Itsna Iftayani; Cahyana Nursidiq; Novita Tri Afifah (LPPM UMRI, 2019)
Abstract Temanggung Regency is one of the largest coffee-producing districts in Central Java. This motivates coffee farmers to expand their business to the production of ground coffee. One business group that focuses on the coffee business is KUB Tegal Makmur Abadi. The problems that exist in KUB are organizational management, low motivation, and marketing which is still limited to the local sector. Based on these problems, several methods used to solve these problems are (1) Focus Group Discussion, (2) Reorganization, (3) Entrepreneurial Motivation, (4) Training, and (5) Monitoring-Evaluation. The results obtained in this mentoring program are KUB Tegal Makmur Abadi feeling (1) The benefits of entrepreneurship assistance programs on business management capabilities, there is already a clear organizational structure formulation and specific assignment of tasks, (2) improvement of marketing skills for KUB members, this can be seen from the ability to create advertisements, manage social media and websites (3) Marketing of Jumprit coffee products that were still in the area of ​​Temanggung Regency has penetrated outside the Island. Keywords: Plastic Waste, Alternative fuel Abstrak Kabupaten Temanggung merupakan salah satu kabupaten pengasil kopi terbesar di Jawa Tengah. Hal ini memotivasi petani kopi untuk mengembangkan usaha hingga ke produksi bubuk kopi. Salah satu kelompok usaha yang fokus pada usaha kopi adalah KUB Tegal Makmur Abadi. Permasalahan yang ada pada KUB adalah manajemen organisasi, motivasi yang rendah dan juga pemasaran yang masih terbatas pada sektor lokal. Berdasarkan permasalahan tersebut, beberapa metode yang digunakan untuk menyelesaikan permasalahan tersebut adalah (1) Focus Group Discussion, (2)Re-organisasi, (3) Motivasi Wirausaha, (4) Pelatihan-pelatihan dan (5) Monitoring-Evaluasi. Hasil yang didapatkan dalam program pendampingan ini adalah KUB Tegal Makmur Abadi merasakan (1) Manfaat program pendampingan kewirausahaan terhadap kemampuan manajemen usaha, sudah ada formulasi struktur organisasi yang jelas dan pembagian tugas secara spesifik, (2) peningkatan keterampilan pemasaran bagi anggota KUB, hal ini dapat dilihat dari kemampuan membuat iklan, mengelola media sosial dan website (3) Pemasaran produk jumprit coffee yang tadinya masih diwilayah Kabupaten Temanggung sudah merambah luar pulau. Keywords: Community Partnership, Arabica coffee, Temanggung